Polyhydric hydroxyl resin, epoxy resin, epoxy resin composition using them, and cured product

JP7644679B2Active Publication Date: 2025-03-12NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021129495
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-06
Publication Date
2025-03-12
Estimated Expiration
2041-08-06

AI Technical Summary

Benefits of technology

【0012】 本発明の多価ヒドロキシ樹脂およびエポキシ樹脂は、高い化学結合エネルギーを持つとともに、分子間力の大きな芳香族エーテルエーテルケトンユニットを主鎖構造中に導入するとともに、一分子中に3個以上の官能基を有する成分を含有する多官能性の構造とすることで、熱分解安定性、耐熱性及び低熱膨張性に優れるとともに、高い芳香族性に由来して、難燃性、低吸湿性に優れた硬化物を与える。また、多量体の混合物とすることで硬化剤等との溶融混合性、溶剤溶解性等のバランスに優れている。これにより、従来のエポキシ樹脂では困難であったエポキシ樹脂組成物を調整する際の取扱い性と優れた硬化物物性の両立が達成される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644679000008
    Figure 0007644679000008
  • Figure 0007644679000009
    Figure 0007644679000009
  • Figure 0007644679000010
    Figure 0007644679000010
Patent Text Reader

Abstract

To provide: a polyhydric hydroxy resin and an epoxy resin that form a cured product excellent in high thermal decomposition stability, high heat resistance, fire retardancy, low hygroscopicity, and the like; an epoxy resin composition of them; and a cured product thereof.SOLUTION: The polyhydric hydroxy resin is obtained by reacting a phenol resin with a benzophenone compound represented by the general formula in the figure of 0.05-0.45 mol per mol of hydroxy groups in the phenol resin. The epoxy resin is obtained from this polyhydric hydroxy resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an epoxy resin which gives a cured product excellent in properties such as high thermal decomposition stability, high heat resistance, low thermal expansion, flame retardancy, and low moisture absorption, a method for producing the same, an epoxy resin composition using the epoxy resin, and a cured product thereof, which are suitably used for insulating materials in the electrical and electronic fields such as semiconductor encapsulation, printed wiring boards, and heat dissipation substrates. [Background technology]

[0002] In recent years, in electronic devices, the high density mounting of semiconductor packages, the high integration and high speed of LSIs, etc. are being promoted, and materials with higher dimensional stability are required. Furthermore, with the progress of single-sided mounting of packages, the reduction of package warpage has also become an important issue, and the development of base resins with lower thermal expansion is required. In response to the above trend, heat dissipation measures for heat generated from elements have become a very important issue. Furthermore, in recent years, in-vehicle electronic components are exposed to high temperature environments for long periods of time, in addition to the conventional physical heat resistance represented by the glass transition point, there is a strong demand for improved chemical heat resistance represented by thermal decomposition stability.

[0003] However, among the conventionally known epoxy resins, none that satisfy these requirements have yet been known. For example, the well-known bisphenol type epoxy resin is liquid at room temperature, has excellent workability, and is easily mixed with curing agents, additives, etc., and is therefore widely used, but has problems with heat resistance and moisture resistance. In addition, phenol novolac type epoxy resins are known as those that have improved heat resistance, but have problems with moisture resistance and impact resistance. In addition, Patent Document 1 proposes an epoxy compound of a phenol aralkyl resin for the purpose of improving moisture resistance and impact resistance, but the heat resistance and flame retardancy are insufficient.

[0004] Patent Document 2 proposes an epoxy resin having a biphenyl and naphthalene structure with an increased content of aromatic structures as one with excellent flame retardancy, but it is still insufficient in terms of thermal decomposition stability and low thermal expansion. Patent Document 3 proposes a naphthol aralkyl type epoxy resin having a structure in which naphthol is linked with a naphthylene group, but since all aromatic structures are naphthalene rings, there is a problem that the viscosity and softening point are high, and the handling and moldability are reduced. Also, it is still insufficient in terms of thermal decomposition stability and low thermal expansion.

[0005] As an example of a material having excellent thermal decomposition stability, Non-Patent Document 1 discloses an epoxy resin having an ether ether ketone group, but because it has strong crystallinity, it has a high melting point of 185°C, making it difficult to adjust the epoxy resin composition and also having problems with moldability. Non-Patent Document 2 also discloses an example of the synthesis of an epoxy resin having the same structure, but the melting point of the obtained epoxy resin is as high as 175°C, and in order to dissolve it in a solvent and use it as a varnish, a highly polar solvent such as DMF, NMP, m-cresol, etc. is required, which imposes significant restrictions on practicality. In addition, since these epoxy resins are bifunctional, there are limitations in heat resistance, represented by curability and glass transition temperature. In addition, Patent Document 4 discloses a polyhydric hydroxy resin having an ether ether ketone group obtained by the reaction of a bisphenol compound with a benzophenone compound, and an epoxy resin obtained therefrom, but there are still problems with heat resistance and moisture resistance. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 63-238122 [Patent Document 2] Japanese Patent Application Publication No. 2000-273281 [Patent Document 3] JP 2004-59792 A [Patent Document 4] Patent No. 5734603 [Non-patent literature]

[0007] [Non-Patent Document 1] SHHwang,et.al.,Polym.Adv.Technol.,12,441(2001) [Non-Patent Document 2] KSLee,et.al.,Bull.Korean Chem.Soc.,22,424(2001) Summary of the Invention [Problem to be solved by the invention]

[0008] Accordingly, an object of the present invention is to provide a polyhydric hydroxy resin, an epoxy resin, and an epoxy resin composition using these which are excellent in moldability and solvent solubility and which give a cured product having excellent properties such as high thermal decomposition stability, high heat resistance, low thermal expansion, flame retardancy, low moisture absorption, and high thermal conductivity, as well as a cured product thereof. [Means for solving the problem]

[0009] That is, the present invention relates to a compound represented by the following general formula (1): [ka] (wherein, A independently represents benzene, biphenyl, or naphthalene, B independently represents a divalent linking group, and R independently represents a hydrocarbon group having 1 to 9 carbon atoms, p is a number from 0 to 2, m is a number from 1 to 2, and n is a number from 1.5 to 15 on average.) and 0.05 to 0.45 moles of a compound represented by the following general formula (2) per mole of hydroxyl group in the phenolic resin: [ka] (wherein each X is independently a halogen atom.) The polyhydric hydroxyl resin is obtained by reacting a benzophenone compound represented by the following formula:

[0010] The epoxy resin is characterized in that it is obtained by reacting the above polyhydric hydroxy resin with epichlorohydrin.

[0011] The present invention further relates to an epoxy resin composition comprising an epoxy resin and a curing agent, characterized in that the epoxy resin is blended as an epoxy resin component.The present invention further relates to an epoxy resin composition comprising an epoxy resin and a curing agent, characterized in that the polyhydric hydroxyl resin is blended as a curing agent component.The present invention also relates to a cured product obtained by curing the epoxy resin composition. Effect of the Invention

[0012] The polyhydric hydroxyl resin and epoxy resin of the present invention have high chemical bond energy, and an aromatic ether ether ketone unit with large intermolecular force is introduced into the main chain structure, and a polyfunctional structure containing a component having three or more functional groups in one molecule is obtained, thereby providing a cured product with excellent flame retardancy and low moisture absorption due to its high aromaticity. In addition, by forming a mixture of polymers, the balance of melt mixability with curing agents, solvent solubility, etc. is excellent. This achieves both easy handling when preparing an epoxy resin composition and excellent cured product properties, which was difficult with conventional epoxy resins. [Brief description of the drawings]

[0013] [Figure 1] 1 is a GPC chart of polyhydric hydroxyl resin A in Example 1. [Diagram 2] 1 is an infrared absorption spectrum of polyhydric hydroxy resin A in Example 1. [Diagram 3] 1 is a GPC chart of polyhydric hydroxy resin B in Example 2. [Figure 4] 1 is a GPC chart of polyhydric hydroxy resin C in Example 3. [Diagram 5] 1 is a GPC chart of epoxy resin A in Example 4. [Figure 6] 1 is an infrared absorption spectrum of epoxy resin A in Example 4. [Figure 7] 1 is a GPC chart of epoxy resin B in Example 5. [Figure 8] 1 is a GPC chart of epoxy resin B in Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below.

[0015] The polyhydric hydroxy resin of the present invention is synthesized by reacting a phenol resin of general formula (1) with a benzophenone compound of general formula (2). [ka] [ka]

[0016] In the general formula (1), A independently represents a benzene, biphenyl, or naphthalene skeleton. R independently represents a hydrocarbon group having 1 to 9 carbon atoms, and specific examples thereof include a methyl group, an ethyl group, an iso-propyl group, a tert-butyl group, a phenyl group, and a benzyl group, but R is preferably a hydrogen atom or a methyl group. p represents a number of 0 to 2, and is preferably 0 or 1. m represents a number of 1 to 2, and is preferably 1 from the viewpoint of low water absorption, and is preferably 2 from the viewpoint of heat resistance. B represents a divalent linking group, and specific examples thereof include a single bond, an oxygen atom, a sulfur atom, a ketone group, a sulfone group, and a divalent hydrocarbon group. Preferred are -CH2-, -CH(Me)-, -CH(φ)-, -C(Me)2-, -CH2-φ-CH2-, -CH(Me)-φ-CH(Me)-, -C(Me)2-φ-C(Me)2-, -CH2-φ-φ-CH2-, and particularly preferred are -CH2-, -CH2-φ-CH2-, and -CH2-φ-φ-CH2-.

[0017] n indicates the average number of repetitions and is 1.5 to 15, preferably 1.7 to 10, and particularly preferably 2.0 to 8. The phenol resin used in the present invention may be a single compound having no molecular weight distribution, or a mixture having a molecular weight distribution.

[0018] In the general formula (1), those in which n is 1 are bisphenols and do not fall under the category of phenolic resins represented by the general formula (1), but can be present to reduce viscosity. If those in which n is 1 are calculated as one of the phenolic resins represented by the general formula (1), it is preferable to have bisphenols in which n is 1 present so that the number average value of n is 1.1 to 15, preferably 1.5 to 10. In this case, from the viewpoint of heat resistance, it is preferable to make the component in which n is 1 50 wt% or less.

[0019] The phenolic resin represented by the general formula (1) preferably has a molecular weight distribution in which n=0 is 0 to 30%, n=1 is 10 to 50%, n=2 is 10 to 60%, and the remainder is n=3 or more. In the formula (1), when m=1, the proportion of n=0 is preferably 5% or less.

[0020] In addition, in the general formula (2), X represents a halogen atom, specifically, a fluorine atom, a chlorine atom, and a bromine atom. The preferred substitution position of the halogen atom is the 4,4'-position relative to the benzophenone skeleton. Specifically, 4,4'-difluorobenzophenone, 4,4'-dichlorobenzophenone, 4,4'-dibromobenzophenone, 3,3'-difluorobenzophenone, 3,3'-dichlorobenzophenone, 3,3'-dibromobenzophenone, 2,2'-difluorobenzophenone, 2,2'-dichlorobenzophenone, and 2,2'-dibromobenzophenone can be mentioned.

[0021] The polyhydric hydroxy resin of the present invention has a hydroxyl group equivalent of preferably 150 to 3000 g / eq., more preferably 170 to 1000 g / eq., and further preferably 190 to 500 g / eq. The softening point is preferably 50 to 300°C, and more preferably 70 to 180°C.

[0022] The polyhydric hydroxy resin of the present invention is obtained by reacting a phenol resin of general formula (1) with a benzophenone compound of general formula (2). The amount of the benzophenone compound used is 0.05 to 0.45 mol, preferably 0.08 to 0.30, and more preferably 0.10 to 0.20, per mol of hydroxyl groups in the phenol resin. If the amount is less than this, the effect of improving heat resistance based on the benzophenone skeleton in the polyhydric hydroxy resin is small, and if it is more than this, the viscosity of the polyhydric hydroxy resin increases, and handling properties such as moldability decrease.

[0023] This reaction is preferably carried out in the presence of a basic catalyst, and at least one compound selected from the group consisting of a tertiary amine compound, a quaternary ammonium compound, an imidazole compound, a tertiary phosphine compound, a quaternary phosphonium compound, an alkali metal hydroxide compound, an alkaline earth metal hydroxide compound, an alkali metal carbonate, and an alkali metal hydrogen carbonate can be used.

[0024] These basic catalysts may be used alone or may be dissolved in water or a solvent in advance and then added to the reaction system. The proportion of the basic catalyst used is usually 0.001 to 10 mol %, preferably 0.05 to 5 mol %, per mol of the phenolic hydroxyl group of the aromatic dihydroxy compound.

[0025] This reaction is usually carried out for 1 to 20 hours at 10 to 250° C. Furthermore, as a reaction solvent, alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, methyl cellosolve, and ethyl cellosolve, benzene, toluene, chlorobenzene, and dichlorobenzene can be used.

[0026] After the reaction is completed, the catalyst may be removed by neutralization, washing with water or the like, and if necessary, the remaining solvent may be removed from the system by washing with water, distillation under reduced pressure or the like, to obtain a polyhydric hydroxyl resin.

[0027] The epoxy resin of the present invention is obtained by reacting the polyhydric hydroxy resin with epichlorohydrin. This reaction can be carried out in the same manner as a normal epoxidation reaction. For example, after dissolving the polyhydric hydroxy resin in excess epichlorohydrin relative to the amount of hydroxyl groups in the polyhydric hydroxy resin, the polyhydric hydroxy resin is reacted for 1 to 10 hours at 50 to 150°C, preferably 60 to 120°C, in the presence of an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide. In this case, the amount of the alkali metal hydroxide used is in the range of 0.8 to 2 moles, preferably 0.9 to 1.2 moles, per mole of hydroxyl groups in the polyhydric hydroxy resin. In addition, epichlorohydrin is used in excess relative to the hydroxyl groups in the polyhydric hydroxy resin, and is usually in the range of 1.5 to 15 moles, preferably 2 to 8 moles, per mole of hydroxyl groups in the polyhydric hydroxy resin. In addition, a quaternary ammonium salt or the like can be added during the reaction. Examples of quaternary ammonium salts include tetramethylammonium chloride, tetrabutylammonium chloride, and benzyltriethylammonium chloride, and the amount of the quaternary ammonium salt added is preferably in the range of 0.1 to 2.0 wt% based on the polyhydroxy resin. If the amount is less than this, the effect of the quaternary ammonium salt is small, and if the amount is more than this, the generation of hardly hydrolyzable chlorine increases, making it difficult to achieve high purification. Furthermore, polar solvents such as dimethyl sulfoxide and diglyme may be used, and the amount of the polar solvent added is preferably in the range of 10 to 200 wt% based on the polyhydroxy resin. If the amount is less than this, the effect of the addition is small, and if the amount is more than this, the volume efficiency decreases, which is not economically preferable. After the reaction is completed, the excess epichlorohydrin is distilled off, and the residue is dissolved in a solvent such as toluene or methyl isobutyl ketone, filtered, washed with water to remove inorganic salts, and then the solvent is distilled off to obtain the desired epoxy resin. This epoxy resin is mainly composed of the compound represented by the general formula (3), but may also contain a glycidyl ether of a compound in which one or more naphthylmethane groups are added to the aromatic ring of the novel polyhydric hydroxy resin represented by the general formula (1).Furthermore, it may also contain a compound in which the epoxy groups in the epoxy resin of the present invention are oligomerized as ether bonds.

[0028] The epoxy resin of the present invention has an epoxy equivalent of preferably 150 to 3000 g / eq., more preferably 180 to 1000 g / eq., and further preferably 200 to 650 g / eq. The softening point is preferably 40 to 200°C, and more preferably 60 to 150°C. The melt viscosity at 150°C is preferably 0.01 to 10 Pa·s, more preferably 0.05 to 5 Pa·s, and particularly preferably 1.0 Pa·s or less. The hydrolyzable chlorine is preferably 1000 ppm or less, and more preferably 300 ppm or less.

[0029] The epoxy resin composition of the present invention comprises an epoxy resin and a curing agent, and contains as an essential component at least one of a polyhydric hydroxy resin obtained by reacting a phenolic resin of the above general formula (1) with a benzophenone compound of the general formula (2) as a curing agent component, and an epoxy resin produced by reacting the polyhydric hydroxy resin of the present invention with epichlorohydrin as an epoxy resin component.

[0030] As the curing agent to be blended in the epoxy resin composition of the present invention, which contains the epoxy resin of the present invention as an essential component, any agent generally known as a curing agent for epoxy resins can be used, such as dicyandiamide, polyhydric phenols, acid anhydrides, aromatic and aliphatic amines, etc.

[0031] Specific examples of polyhydric phenols include dihydric phenols such as bisphenol A, bisphenol F (mixture of isomers), 4,4'-dihydroxydiphenylmethane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfone, fluorene bisphenol, 4,4'-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, hydroquinone, resorcin, 1,5-naphthalenediol, 1,6-naphthalenediol, 2,6-naphthalenediol, and 2,7-naphthalenediol, and trihydric or higher phenols such as tris(hydroxyphenyl)methane mixtures, tris-(4-hydroxyphenyl)methane, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, phenol novolac, o-cresol novolac, naphthol novolac, and polyvinylphenol. Further, there are polyhydric phenolic compounds synthesized by phenols such as phenol, o-cresol, monohydric phenols such as naphthols, dihydric phenols such as bisphenol A, bisphenol F, bisphenol S, fluorene bisphenol, 4,4'-biphenol, 2,2'-biphenol, hydroquinone, resorcin, naphthalenediol, and condensation agents such as formaldehyde, acetaldehyde, benzaldehyde, p-hydroxybenzaldehyde, 1,4-dihydroxymethylbenzene, 1,4-dimethoxymethylbenzene, 1,4-bischloromethylbenzene, 4,4'-dihydroxymethylbiphenyl, 4,4'-dimethoxymethylbiphenyl, 4,4'-bischloromethylbiphenyl, 1,5-bischloromethylnaphthalene, 1,4-bischloromethylnaphthalene, etc. In addition, the polyhydric hydroxy resin of the present invention may be used as a part or all of the curing agent.

[0032] Examples of the acid anhydride include phthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylhimic anhydride, nadic anhydride, and trimellitic anhydride.

[0033] Furthermore, the amines include aromatic amines such as 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylsulfone, m-phenylenediamine, p-xylylenediamine, and 1,5-diaminonaphthalene, and aliphatic amines such as ethylenediamine, hexamethylenediamine, diethylenetriamine, and triethylenetetramine.

[0034] Among the curing agents, it is preferable to use a phenolic curing agent from the viewpoints of electrical insulation, low moisture absorption, high thermal conductivity, low thermal expansion, etc. In particular, from the viewpoints of thermal decomposition stability, low thermal expansion, and low moisture absorption of the cured product, it is preferable to use an aralkyl-type phenolic resin obtained by condensing phenols with 1,4-dihydroxymethylbenzene, 4,4'-dimethoxymethylbiphenyl, etc. In addition, from the viewpoints of heat resistance and high thermal conductivity, polyhydric phenolic compounds such as phenol novolac, tris(hydroxyphenyl)methanes, and 1,1,2,2-tetrakis(hydroxyphenyl)ethanes are preferable.

[0035] The resin composition of the present invention can be used by mixing one or more of the above curing agents. In the case of a resin composition containing the polyhydric hydroxyl resin of the present invention as an essential component, the blending amount of the polyhydric hydroxyl resin of the present invention is preferably in the range of 50 to 100 wt%, preferably 70 to 100 wt%, of the total curing agent. If the blending amount is less than this, the effect of improving the high thermal decomposition stability, high heat resistance, low thermal expansion, flame retardancy, low moisture absorption, high thermal conductivity, etc., when the cured product is obtained is small.

[0036] In addition, in the epoxy resin composition of the present invention, other kinds of epoxy resins may be blended as epoxy resin components in addition to the epoxy resin of the present invention. In this case, any ordinary epoxy resin having two or more epoxy groups in the molecule can be used as the epoxy resin. Examples include dihydric phenols such as bisphenol A, 4,4'-dihydroxydiphenylmethane, bisphenol A, bisphenol F (isomer mixture), 4,4'-dihydroxydiphenylmethane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfone, fluorene bisphenol, 4,4'-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, hydroquinone, resorcin, 1,5-naphthalenediol, 1,6-naphthalenediol, 2,6-naphthalenediol, and 2,7-naphthalenediol, or phenol novolac, bisphenol A novolac, o-cresol novolac, m- Examples include cresol novolac, p-cresol novolac, xylenol novolac, poly-p-hydroxystyrene, tris(hydroxyphenyl)methane mixture, tris-(4-hydroxyphenyl)methane, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, fluoroglycinol, pyrogallol, t-butylpyrogallol, allylated pyrogallol, polyallylated pyrogallol, 1,2,4-benzenetriol, 2,3,4-trihydroxybenzophenone, phenol aralkyl resin, aralkyl-type phenol resin having a 4,4'-biphenylene group, dicyclopentadiene resin, and other trivalent or higher phenols, or glycidyl ethers derived from halogenated bisphenols such as tetrabromobisphenol A. These epoxy resins can be used alone or in combination of two or more.

[0037] In the case of a composition containing the epoxy resin of the present invention as an essential component, the blending amount of the epoxy resin of the present invention is preferably in the range of 50 to 100 wt %, and more preferably 70 to 100 wt %, of the total epoxy resin. If the blending amount is less than this range, the effects of improving the high thermal decomposition stability, high heat resistance, low thermal expansion, flame retardancy, low moisture absorption, high thermal conductivity, etc., of the cured product are small.

[0038] The compounding ratio of the epoxy resin and the curing agent is preferably in the range of 0.8 to 1.5 in terms of the equivalent ratio of the epoxy group to the functional group in the curing agent. Outside this range, there is a possibility that unreacted epoxy groups or functional groups in the curing agent may remain after curing.

[0039] In addition, an appropriate amount of inorganic filler can be blended into the epoxy resin composition of the present invention. Examples of inorganic fillers include metals, metal oxides, metal nitrides, metal carbides, metal hydroxides, and carbon materials. Examples of metals include silver, copper, gold, platinum, and zircon; examples of metal oxides include silica, alumina, magnesium oxide, titanium oxide, and tungsten trioxide; examples of metal nitrides include boron nitride, aluminum nitride, and silicon nitride; examples of metal carbides include silicon carbide; examples of metal hydroxides include aluminum hydroxide and magnesium hydroxide; and examples of carbon materials include carbon fibers, graphitized carbon fibers, natural graphite, artificial graphite, spherical graphite particles, mesocarbon microbeads, whisker-like carbon, microcoil-like carbon, nanocoil-like carbon, carbon nanotubes, and carbon nanohorns. Examples of the shape of the inorganic filler include crushed, spherical, whisker-like, and fibrous fillers, but spherical fillers are preferred in order to achieve a high filling rate. In order to ensure the insulating property and high thermal conductivity of the epoxy resin cured product, metal oxides are preferred as the inorganic filler, and alumina, boron nitride, and aluminum nitride are particularly preferred. These inorganic fillers may be blended alone or in combination of two or more. In addition, the inorganic filler may be treated with a conventional coupling agent for the purposes of improving the wettability between the inorganic filler and the epoxy resin, reinforcing the interface of the inorganic filler, improving dispersibility, etc.

[0040] The amount of inorganic filler is preferably 50wt% or more, more preferably 70wt% or more. If it is less than this, the effect of improving thermal conductivity is small. Also, from the viewpoint of low moisture absorption and high solder heat resistance, the amount of inorganic filler used is usually 75wt% or more, and particularly preferably 80wt% or more.

[0041] In the epoxy resin composition of the present invention, a conventionally known curing accelerator can be used. Examples include amines, imidazoles, organic phosphines, Lewis acids, etc., specifically, tertiary amines such as 1,8-diazabicyclo(5,4,0)undecene-7, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, and tris(dimethylaminomethyl)phenol, imidazoles such as 2-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, and 2-heptadecylimidazole, organic phosphines such as tributylphosphine, methyldiphenylphosphine, triphenylphosphine, diphenylphosphine, and phenylphosphine, tetra-substituted phosphonium and tetra-substituted borates such as tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium ethyltriphenylborate, and tetrabutylphosphonium tetrabutylborate, and tetraphenylboron salts such as 2-ethyl-4-methylimidazole tetraphenylborate and N-methylmorpholine tetraphenylborate. The amount added is usually within the range of 0.2 to 10 parts by weight based on 100 parts by weight of the epoxy resin.

[0042] Furthermore, the epoxy resin composition of the present invention may contain oligomers or polymer compounds such as polyesters, polyamides, polyimides, polyphenylene ethers, polyetherimides, polyphenylene sulfides, polyethersulfones, liquid crystal polymers, polyethers, polyurethanes, petroleum resins, indene coumarone resins, and phenoxy resins, and may contain additives such as pigments, flame retardants, thixotropy-imparting agents, coupling agents, and flowability improvers. Examples of pigments include organic or inorganic extender pigments and scaly pigments. Examples of thixotropy-imparting agents include silicone-based, castor oil-based, aliphatic amide wax, oxidized polyethylene wax, and organic bentonite-based agents. Furthermore, if necessary, the resin composition of the present invention may contain additives such as halogen-based flame retardants such as brominated epoxy, phosphorus-based flame retardants such as red phosphorus, phosphate esters, and phosphorus-atom-containing epoxy resins, flame retardant assistants such as antimony trioxide, release agents such as carnauba wax and ester wax, coupling agents such as γ-glycidoxypropyltrimethoxysilane, colorants such as carbon black, stress reducing agents such as silicone oil, lubricants such as calcium stearate, and additives such as epoxy silanes, amino silanes, ureido silanes, vinyl silanes, alkyl silanes, organic titanates, and aluminum alcoholates.

[0043] The epoxy resin composition of the present invention can generally be obtained by thoroughly mixing the above-mentioned epoxy resin, curing agent component and other components in predetermined amounts using a mixer or the like, kneading the mixture using a mixing roll, an extruder or the like, cooling and pulverizing the mixture.

[0044] Alternatively, the above blending components can be dissolved in an aromatic solvent such as benzene, toluene, xylene, chlorobenzene, etc., a ketone solvent such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc., an aliphatic hydrocarbon solvent such as hexane, heptane, methylcyclohexane, etc., an alcohol solvent such as ethanol, isopropanol, butanol, ethylene glycol, etc., an ether solvent such as diethyl ether, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether, etc., or a polar solvent such as N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, N-methylpyrrolidone, etc. to form a varnish-like epoxy resin composition. The varnish-like epoxy resin composition can also be impregnated into a fibrous filler such as glass fiber, carbon fiber, aramid fiber, etc., and then dried to remove the organic solvent to form a prepreg-like epoxy composition.

[0045] To obtain a cured product using the epoxy resin composition of the present invention, for example, methods such as transfer molding, press molding, cast molding, injection molding, extrusion molding, etc., are applied. In addition, a method such as vacuum pressing is used as a method for curing a prepreg-like epoxy resin composition. The temperature in this case is usually in the range of 120 to 220°C.

[0046] The epoxy resin cured product of the present invention can be obtained by heat curing by the above molding method, and the molding temperature is usually 80°C to 250°C, and the molding time is 1 minute to 20 hours. In order to increase the crystallinity of the epoxy resin cured product, it is desirable to cure it at a low temperature for a long time. The preferred curing temperature is in the range of 100°C to 180°C, more preferably 120°C to 160°C. In addition, the preferred curing time is 10 minutes to 6 hours, more preferably 30 minutes to 3 hours. Furthermore, after molding, the crystallinity can be further increased by post-curing. Usually, the post-cure temperature is 130°C to 250°C, and the time is in the range of 1 hour to 20 hours, but it is preferable to perform post-cure at a temperature 5°C to 40°C lower than the endothermic peak temperature in differential thermal analysis for 1 hour to 24 hours.

[0047] The epoxy resin cured product of the present invention can be laminated with a different type of substrate. The substrate to be laminated can be in the form of a sheet or film, and examples of the substrate include metal substrates such as copper foil, aluminum foil, and stainless steel foil, and polymer substrates such as polyethylene, polypropylene, polystyrene, polyacrylate, polymethacrylate, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, liquid crystal polymer, polyamide, polyimide, and polytetrafluoroethylene. EXAMPLES

[0048] The present invention will now be described in more detail with reference to the following examples. In the examples, the physical properties were measured by the following methods.

[0049] 1) GPC measurement The analysis was performed using a HLC-8320 GPC apparatus (manufactured by Tosoh Corporation) and columns: 2 TSKgel SuperHZ2500 and 2 TSKgel SuperHZ2000 (both manufactured by Tosoh Corporation), with a solvent of tetrahydrofuran, a flow rate of 0.35 ml / min, a temperature of 40°C, and a detector of RI.

[0050] 2) Melt Viscosity The viscosity was measured at 150° C. using a Brookfield CAP2000H rotational viscometer.

[0051] 3) Measurement of hydroxyl equivalent Using a potentiometric titrator, acetylation was carried out with 1.5 mol / L acetyl chloride in 1,4-dioxane as a solvent, and the excess acetyl chloride was decomposed with water and titrated with 0.5 mol / L potassium hydroxide.

[0052] 4) Measurement of epoxy equivalent A potentiometric titrator was used, and methyl ethyl ketone was used as the solvent. Tetraethylammonium bromide acetate solution was added, and the measurement was performed using a 0.1 mol / L perchloric acid-acetic acid solution in the potentiometric titrator.

[0053] 5) Hydrolyzable chlorine 0.5 g of sample was dissolved in 30 ml of dioxane, 10 ml of 1N-KOH was added, and the mixture was boiled under reflux for 30 minutes. The mixture was then cooled to room temperature, and 100 ml of 80% acetone water was added. The solution was then subjected to potentiometric titration with a 0.002N-AgNO3 aqueous solution.

[0054] 6) Infrared absorption spectrum The measurement was performed by the KBr pellet method using a JASCO FT / IR-6100 infrared absorption analyzer.

[0055] 7) Pyrolysis temperature, thermogravimetry measurement Using a Hitachi High-Tech Science TG / DTA7300 thermogravimetry device, the pyrolysis temperature and the residual carbon ratio at 700°C (10% weight loss temperature) were determined under nitrogen flow at a heating rate of 10°C / min.

[0056] 8) Linear expansion coefficient, glass transition temperature (Tg) The measurements were performed using a Hitachi High-Tech Science TMA7100 thermomechanical measuring device at a heating rate of 10° C. / min.

[0057] 9) Water absorption rate A disk with a diameter of 50 mm and a thickness of 3 mm was molded, and after post-curing, it was left to absorb moisture for 94 hours at 133°C and 3 atm, after which the weight change rate was recorded.

[0058] Example 1 A 1-L separable flask was charged with 100 g (number of moles of hydroxyl groups: 0.95 mol) of phenol novolak (phenolic resin A; manufactured by Nippon Steel Chemical & Material Co., Ltd.; hydroxyl equivalent: 105 g / eq.; in formula (1), A = benzene ring (hereinafter, referred to as φ), B = -CH2-, and n = 0 is absent (0%), n = 1 is 11.8%, n = 2 is 57.5%, n = 3 is 20.7%, n = 4 is 6.1%, n = 5 is 2.3%, and n ≥ 6 is 1.5%; the average value of n is 2.4), 30 g (0.14 mol) of 4,4'-difluorobenzophenone (DFBP), 22.6 g of anhydrous potassium carbonate, and 300 g of N-methylpyrrolidone (NMP), and the mixture was reacted for 4 hours at 140°C under a nitrogen stream while distilling off the generated water. After the reaction, 19.6 g of acetic acid was added to neutralize the mixture, and then NMP was distilled off under reduced pressure at 160°C. The mixture was then washed with water and dehydrated under reduced pressure to obtain 115 g of solid resin (polyhydroxy resin A). The OH equivalent was 198 g / eq., the softening point was 54°C, and the melt viscosity at 150°C was 1.2 Pa s. The GPC chart is shown in Figure 1, and the infrared absorption spectrum in Figure 2.

[0059] Example 2 In a 1-L separable flask, 67 g (number of moles of hydroxyl groups: 0.62 mol) of naphthalenediol aralkyl resin (phenolic resin B; Nippon Steel Chemical & Material Co., Ltd., SN-395, hydroxyl equivalent: 108 g / eq., in formula (1), A=naphthalene, B=-CH2-φ-CH2-, and n=0 is 21.1%, n=1 is 27.6%, n=2 is 19.2%, n=3 is 12.0%, n=4 is 7.4%, n=5 is 4.5%, n=6 is 2.9%, n=7 is 1.5%, and n≧8 is 2.4%; the average value of n is 2.0) were charged, 20 g (0.09 mol) of DFBP, 15.1 g of anhydrous potassium carbonate, and 200 g of NMP were charged, and the mixture was reacted for 4 hours at 130° C. under a nitrogen stream while distilling off the generated water. After the reaction, 13.1 g of acetic acid was added to neutralize the mixture, and NMP was then distilled off at 160°C under reduced pressure. The mixture was then washed with water and dehydrated under reduced pressure to obtain 80 g of a solid resin (polyhydroxy resin B). The OH equivalent was 217 g / eq. and the softening point was 160°C. The GPC chart is shown in Figure 3.

[0060] Example 3 In a 1 L separable flask, 67 g (number of moles of hydroxyl groups: 0.32 mol) of biphenyl aralkyl resin (phenolic resin C; manufactured by Meiwa Kasei, MEH-7851, hydroxyl equivalent: 210 g / eq., in formula (1), A = biphenyl, B = -CH2-φ-φ-CH2-, and n = 0 is absent (0%), n = 1 is 36.7%, n = 2 is 24.7%, n = 3 is 14.3%, n = 4 is 8.7%, n = 5 is 5.4%, n ≧ 6 is 7.6%; average value of n is 2.4) were charged, 20 g (0.09 mol) of DFBP, 15.1 g of anhydrous potassium carbonate, and 200 g of NMP were charged, and the mixture was reacted for 4 hours at 110 ° C. under a nitrogen stream while distilling off the generated water. After the reaction, 13.1 g of acetic acid was added to neutralize the mixture, and then NMP was distilled off under reduced pressure at 160°C. The mixture was then washed with water and dehydrated under reduced pressure to obtain 86 g of solid resin (polyhydroxy resin C). The OH equivalent was 290 g / eq., the softening point was 80°C, and the melt viscosity at 150°C was 1.6 Pa s. The GPC chart is shown in Figure 4.

[0061] Example 4 45g of the polyhydric hydroxy resin A obtained in Example 1, 420g of epichlorohydrin, and 63.5g of diethylene glycol dimethyl ether were charged, and 19.6g of 48.6% aqueous sodium hydroxide solution was dropped at 65°C under reduced pressure (about 130 Torr), and the reaction was carried out for 4 hours. Thereafter, epichlorohydrin and the generated water were distilled off at 85°C under reduced pressure, and 200g of toluene was added to dissolve the mixture, and the generated salt was removed by filtration. After further washing with water, 0.9g of 48.8% aqueous potassium hydroxide solution was added, and the reaction was carried out at 80°C for 2 hours. Thereafter, after repeated washing with water, toluene was removed under reduced pressure, and 54g of solid resin (epoxy resin A) was obtained. The epoxy equivalent was 252g / eq., the softening point was 70°C, the melt viscosity at 150°C was 0.31 Pa·s, and the hydrolyzable chlorine was 20ppm. The GPC chart is shown in FIG. 5, and the infrared absorption spectrum is shown in FIG. 6.

[0062] Example 5 40 g of the polyhydric hydroxy resin B obtained in Example 2, 340 g of epichlorohydrin, and 70 g of diethylene glycol dimethyl ether were charged, and 15.9 g of 48.8% aqueous sodium hydroxide solution was dropped at 65°C under reduced pressure (about 130 Torr) over 3 hours. During this time, the water generated was removed from the system by azeotropy with epichlorohydrin, and the distilled epichlorohydrin was returned to the system. After the dropwise addition was completed, the reaction was continued for another hour to dehydrate. Then, epichlorohydrin was removed under reduced pressure, 200 g of methyl isobutyl ketone (MIBK) was added and dissolved therein, the salt generated was removed by filtration, and the mixture was washed with water, after which 0.7 g of 48.8% aqueous potassium hydroxide solution was added and reacted at 80°C for 2 hours. After repeated washing with water, MIBK was removed from the MIBK layer under reduced pressure to obtain 34 g of solid resin (epoxy resin B). The epoxy equivalent was 238 g / eq., the softening point was 69°C, the melt viscosity at 150°C was 0.06 Pa s, and the hydrolyzable chlorine content was 40 ppm. The GPC chart is shown in Figure 7.

[0063] Example 6 40 g of the polyhydric hydroxy resin C obtained in Example 3, 255 g of epichlorohydrin, and 50 g of diethylene glycol dimethyl ether were charged, and 11.9 g of 48.8% aqueous sodium hydroxide solution was dropped at 65°C under reduced pressure (about 130 Torr) over 3 hours. During this time, the water generated was removed from the system by azeotropy with epichlorohydrin, and the distilled epichlorohydrin was returned to the system. After the dropwise addition was completed, the reaction was continued for another 1 hour to dehydrate. Then, epichlorohydrin was removed under reduced pressure, 200 g of MIBK was added and dissolved therein, the salt generated was removed by filtration, and further washing was performed, after which 0.5 g of 48.8% aqueous potassium hydroxide solution was added and reacted at 80°C for 2 hours. Then, after repeated washing with water, MIBK was removed from the MIBK layer under reduced pressure to obtain 38 g of solid resin (epoxy resin C). The epoxy equivalent was 487 g / eq., the softening point was 72°C, the melt viscosity at 150°C was 0.37 Pa s, and the hydrolyzable chlorine content was 150 ppm. The GPC chart is shown in Figure 8.

[0064] Reference example 1 A 1L separable flask was charged with 75g (0.375mol) of bisphenol F (manufactured by Honshu Chemical), 27.5g (0.125mol) of DFBP, 20.7g of anhydrous potassium carbonate, and 270g of NMP, and reacted for 4 hours at 140℃ under a nitrogen stream while distilling off the generated water. After the reaction, 18.0g of acetic acid was added for neutralization, and then NMP was distilled off under reduced pressure at 160℃. After that, it was washed with water and dehydrated under reduced pressure to obtain 95g of solid resin (polyhydroxy resin D). The OH equivalent was 196g / eq., and the melt viscosity at 150℃ was 0.8Pa·s.

[0065] Reference example 2 45g of polyhydric hydroxy resin D obtained in Reference Example 1, 420g of epichlorohydrin, and 63.5g of diethylene glycol dimethyl ether were charged, and 19.4g of 48.6% aqueous sodium hydroxide solution was dropped at 65°C under reduced pressure (about 130 Torr), and reacted for 4 hours. Then, epichlorohydrin and generated water were distilled off at 85°C under reduced pressure, and 200g of toluene was added to dissolve it, and the generated salt was removed by filtration. After further washing with water, 0.9g of 48.8% aqueous potassium hydroxide solution was added, and reacted at 80°C for 2 hours. Then, after repeated washing with water, toluene was removed under reduced pressure, and 52g of solid resin (epoxy resin D) was obtained. The epoxy equivalent was 254g / eq., the softening point was 50°C, the melt viscosity at 150°C was 0.21 Pa·s, and the hydrolyzable chlorine was 220ppm.

[0066] Examples 7 to 9 and Comparative Examples 1 and 2 As the epoxy resin component, the epoxy resins (epoxy resins A to D) synthesized in Examples 4 to 6 and Reference Example 2, and o-cresol novolac type epoxy resin (epoxy resin E; Nippon Kayaku Co., Ltd., EOCN-1020, epoxy equivalent 200, softening point 55°C) were used, and phenol novolac (AICA Corporation, BRG-557, OH equivalent 104, softening point 83°C) was used as the curing agent, and triphenylphosphine was used as the curing accelerator, and mixed in the formulation shown in Table 1, and kneaded at 100°C to obtain an epoxy resin composition. This epoxy resin composition was used to mold at 150°C, and post-cured at 175°C for 6 hours to obtain a cured product test piece, which was then subjected to various physical property measurements. The evaluation results are shown in Table 1. The blend amounts shown in Table 1 are parts by weight.

[0067] [Table 1]

Claims

1. The following general formula (1): 【Chemistry 1】 (wherein, A independently represents benzene, biphenyl, or naphthalene, B independently represents a divalent linking group, R independently represents a hydrocarbon group having 1 to 9 carbon atoms, p represents a number from 0 to 2, m represents a number from 1 to 2, and n represents a number from 1.5 to 15 on average.) and 0.05 to 0.45 moles of a phenolic resin represented by the following general formula (2), per mole of hydroxyl group in the phenolic resin: 【Chemistry 2】 (wherein X represents a halogen atom.) 2. A polyhydric hydroxy resin obtained by reacting a benzophenone compound represented by the following formula:

2. In the general formula (1), the divalent linking group is -CH 2 -, -CH(Me)-, -CH(φ)-, -C(Me) 2 --, --CH 2 -φ-CH 2 -, -CH(Me)-φ-CH(Me)-, -C(Me) 2 -φ-C(Me) 2 --, --CH 2 -φ-φ-CH 2 2. The polyhydric hydroxyl resin according to claim 1, wherein φ is a group selected from the group consisting of benzene rings.

3. 3. An epoxy resin obtained by reacting the polyhydric hydroxy resin according to claim 1 or 2 with epichlorohydrin.

4. 3. An epoxy resin composition comprising an epoxy resin and a curing agent, the epoxy resin composition comprising the polyhydric hydroxyl resin according to claim 1 or 2 as a curing agent component.

5. 4. An epoxy resin composition comprising an epoxy resin and a curing agent, the epoxy resin composition comprising the epoxy resin according to claim 3 as an epoxy resin component.

6. A cured product obtained by curing the epoxy resin composition according to claim 4 or 5.

Citation Information

Patent Citations

  • Illuminator

    JP1982034603A

  • Epoxy resin and production thereof

    JP1988238122A

  • Epoxy resin composition and semiconductor device

    JP2000273281A

  • Polyhydroxy resin, epoxy resin, method for producing the same, epoxy resin composition and cured product using the same

    JP2004059792A

  • Thermosetting resin composition

    JP2011102339A